Sustainable synthesis of ciclopentene derivatives through multicomponent reactions in continuous flow regime - Broterson, Yoisel Bueno (Universidade Federal de São Carlos, 2020)
Sustainable chemistry has gained relevance in recent years, not only in the fine chemical industry, but also in organic synthesis. This new conception of chemistry allows the development of environmentally friendly processes, by minimizing waste generation as well as in reducing the handling of hazardous chemical reagents. However, this approach encourages the use of "sustainable or green" substrates and solvents. In this context, the use of continuous flow has been extended at an exponential rate in organic synthesis, due to the various applications to the synthesis of derivatives of natural products of interest to the pharmaceutical industry. In order to contribute in the area, this project aimed to develop a new stereoselective methodology for the synthesis of tetrasubstituted cyclopentenes through sustainable approach. Combination of organocatalysis and multicomponent reactions as synthesis tools was chosen. Both methodologies allowed the use of green solvents, as well as the incorporation of continuous flow techniques in the substitution of batch methods. The multicomponent stage represented significant advances in the development of a more sustainable methodology. Finally, the designed methodology can be considered as a sustainable protocol for the synthesis of analogues of natural products, enantiomerically enriched, quick and efficiently.
Síntese sustentável de derivados de ciclopenteno através de reações multicomponentes em regime de fluxo contínuo
Keywords: Sustainable chemistry; Organocatalysis; Multicomponent reactions; Continuous flow chemistry; Ciclopentene derivatives; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA